2016
DOI: 10.4236/oalib.1102839
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of rsSNPs Associated with Hypertension Using In-Silico Bioinformatics Tools

Abstract: Genetic epidemiological studies have suggested that several genetic variants increase the risk for hypertension. It is likely that a number of genes rather than a single gene account for the heritability of this complex disorder. However, the genetic analysis of hypertension produced complex, inconsistent and nonreproducible results, which makes it difficult to draw conclusions about the association between specific genes and hypertension. Material and methods: In this study, we aimed to analyze SNPs that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The methods used in this study revealed the importance of using various algorithms with different prediction capacities to estimate the effect of variations on structural and functional levels. Using a single bioinformatic tool to predict potentially pathogenic nsSNPs may not be significant [45]. Hence, the present study was based on multiple computational tools including SIFT, Poly-Phen1/2, MAAP, PhD-SNP, PredictSNP, SNAP, ConSurf, ModPred, I-Mutant2.0, and MUpro in order to identify the most deleterious nsSNPs in RETN gene.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used in this study revealed the importance of using various algorithms with different prediction capacities to estimate the effect of variations on structural and functional levels. Using a single bioinformatic tool to predict potentially pathogenic nsSNPs may not be significant [45]. Hence, the present study was based on multiple computational tools including SIFT, Poly-Phen1/2, MAAP, PhD-SNP, PredictSNP, SNAP, ConSurf, ModPred, I-Mutant2.0, and MUpro in order to identify the most deleterious nsSNPs in RETN gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all SNPs are associated with human diseases. Coding region SNPs are known as nsSNPs or non-synonymous SNPs which have greater impact on the protein structure, function, stability, and solubility through amino acid replacement in protein sequence 5,6 . These nsSNPs can be categorized as either 'pathogenic/deleterious' causing disease phenotypes, or 'tolerated/neutral' causing no effect on protein structure, function or stability 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference of a single nucleotide, i.e., A, T, C, or G at a specific position in the genome is defined as an SNP. Human genes contain about 93% SNPs [ 11 ]. Coding, non-coding, or intergenic regions of genes have SNPs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%